2014
DOI: 10.1177/1039856214539859
|View full text |Cite
|
Sign up to set email alerts
|

We need to talk about depot: effect of Community Treatment Order on depot antipsychotic medication compliance

Abstract: The current study highlighted that while Community Treatment Order may be a reasonable short-term tool to encourage patients' compliance at an early treatment stage, ongoing effort should be put into improving patients' attitude towards depot medications to ensure a better long-term outcome for individuals with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…One article reported secondary outcomes from an RCT. 31 The remaining 9 papers 32 40 reported on a wide range of other outcomes (for example, medication, access to secondary services, and mortality), with mixed, but largely negative, results as to CTO benefit.…”
Section: Resultsmentioning
confidence: 99%
“…One article reported secondary outcomes from an RCT. 31 The remaining 9 papers 32 40 reported on a wide range of other outcomes (for example, medication, access to secondary services, and mortality), with mixed, but largely negative, results as to CTO benefit.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that workers need to find a way to ‘reach through’ the psychotic beliefs, to engage the person meaningfully, to gain their trust, to reach past the threat and the authority that they represent as part of their role; processes described by Banks, Stroud and Doughty [ 63 ] as ‘personalisation’. Of relevance to this need, Suetani, Foo and Wilson’s [ 64 ] study involving 90 mental health patients found a trend for greater compliance to depot medication by those not on a CTO compared with those who were. They concluded that CTOs become a double-edged sword because, while forced cooperation might lead some patients to accept medication in the long-term, other patients might associate the experience with a loss of autonomy and develop negative attitudes to medication more generally.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, one of our worker participants argued for more first episode psychosis patients to be put on CTOs so that they would receive earlier, more assertive treatment and avoid the long-term negative consequences of untreated mental illness. What such a view fails to appreciate is the damage to trust, worker-patient relationships and engagement with healthcare providers that such a path can bring, as described by many of our patient participants, and noted in other studies [ 9 , 11 14 , 35 , 36 ]. O’Hagan refers to coercion as the ‘elephant in the recovery room’ [ 52 ] and that, to make progress, we need to have more open dialogue about paternalism and coercion and their association with the moral framings that both workers and patients use to describe their experience of CTOs.…”
Section: Discussionmentioning
confidence: 81%
“…Most research has shown that CTOs do not reduce readmission rates or duration, or increase time to readmission or treatment adherence [ 17 , 32 34 ]. A study of 90 patients by Suetani et al [ 35 ] found a trend for greater compliance to intra-muscular depot medication by those not on a CTO compared with those who were. They concluded that CTOs become a double-edged sword because, while forced cooperation might lead some patients to accept medication in the long-term, other patients might associate the experience with the loss of autonomy and develop negative attitudes to medication, help-seeking from mental health services and indeed the medical profession, more generally.…”
Section: Introductionmentioning
confidence: 99%